HUBUNGAN PENGETAHUAN GIZI SEIMBANG, POLAMAKAN DAN AKTIVITAS FISIK DENGAN STATUS GIZILEBIH PADA REMAJA DI MAN 21 JAKARTA UTARA - Bella Maharanny PrillyanSari, (2020)
Background : Overweight of was more risk fifth main cause of global death. In 2018, Indonesia has a prevalence of overweight in adolescents based on age 16-18 years of 9.5%. Overweight that occurs in adolescents will continue into adulthood and can cause several diseases such as cardiovascular, diabetes mellitus, and cancer. Objectives : This research aims to analyze the relationship between knowledge about nutrition balanced relations, a diet, and physical activity with overweight in adolescents at MAN 21 North Jakarta. Method : This research is an analytic study with a cross-sectional design. The total sample of 57 respondents were taken by simple random sampling technique. The research instrument uses a balanced nutrition knowledge questionnaire, semi-quantitative food frequency questionnaire, physical activity level questionnaire, and anthropometric data. Results: Based on univariate results as many as 80.7% of adolescents had knowledge of well balanced nutrition, 63.2% of adolescents with a good diet, 52.6% of adolescents with light physical activity, and 78.9% of adolescents with normal nutritional status. For the results of bivariate analysis using the Chi square test to obtain knowledge of balanced nutrition (p = 0.042), diet (p = 0.040), physical activity (p = 0.038). Conclusion : There is a correlation between knowledge of balanced nutrition, diet, and physical activity with over nutritional status in adolescents at MAN 21 North Jakarta.